Maladministration Law Enforcement: The Authority of the Ombudsman in a Fair Public Service Dispute Resolution Mechanism - Yasid, Akhmadi; Poesoko, Herowati; Dwi Hastri, Evi (International Asia Of Law and Money Laundering, 2024)
Maladministration law enforcement is a crucial issue in realizing excellent public services. The Ombudsman, as an independent institution, plays an important role in resolving public service disputes efficiently and fairly. Law of the Republic of Indonesia Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia in Article 26 Paragraph (2) point a triggers a vague norm that illustrates that the Ombudsman is not based on definite considerations and can be measured based on the theory of legal certainty. So that this will trigger articles that have the potential to abuse authority in the organ of the Ombudsman of the Republic of Indonesia (ORI). This type of research is normative juridical with a statutory approach and a concept approach, resulting in the fact that the Ombudsman of the Republic of Indonesia (ORI) has broad authority in handling public service disputes, including in cases of maladministration. Namely those that are not in accordance with the principles of good governance, including abuse of authority, negligence, discrimination, delay, and other actions that can harm the community. Law enforcement against maladministration can be carried out if there is legal certainty in determining the status of examinations that can be continued or not based on the concept of good governance so as to create justice.